نمذجة قياسية لمعدلات البطالة في الجزائر دراسة قياسية للفترة 1980- 2014 - رحماني, موسى; بقاط, حنان (University of Eloued جامعة الوادي, 2016)
كانت ولا تزال البطالة من ابرز المشكلات الاقتصادية والاجتماعية التي تعاني منها الجزائر حيث شهد الاقتصاد الجزائري معدلات بطالة مرتفعة على مر العقود الثلاثة الماضية تراوح معدلها من 8.7 % إلى 29.49 %، و لقد استحوذ الشباب الذين تقل أعمارهم عن 30 سنة حوالي 70 % و منهم 75 هم طالبي منصب عمل لأول مرة ولهذا أصبح حل مشكلة البطالة من اكبر التحديات التنموية التي تواجهها الجزائر. Abstract: The Unemployment is considered the most prominent economic and social problems plaguing in Algeria, Where the Algerian economy is witnessing high rates of unemployment over the past of three decades, the rate ranged from 8.7 % to 29.49 %. And they has acquired a young people under the age of 30 years about 70 % to 75 % of them are asylum jobs for the first time For this solution to unemployment it became one of the biggest development challenges faced by Algeria problem.
Modeling record rates of unemployment in Algeria 2014 An Empirical study for the period 1980
مجلة رؤى المجلد السادس العدد الأول
Keywords: بطالة، سوق العمل، عرض العمل، طلب على العمل; The unemployment, labor market, labor supply ,demand labor demand (JEL) Classification : C01,E24